(untitled) (American Journal of Islam and Society, 2016)
The title of Kecia Ali’s latest book, The Lives of Muhammad, suggests that it is another biography of the Prophet. And it very much is that book, not as biography but as historiography, cultural study, and the methods of the Study of Religion. By focusing narrowly on the material, she is able to be expansive in her thought and raise several important issues in the study of Muhammad’s life, both from the perspective of the believer and the non-believer. Most importantly, and what makes this book particularly successful, is that she recognizes conflict and contradiction without offering resolution. The result is a work that can be extremely useful in classroom settings, in addition to making a valuable contribution to what we think about the meanings of Muhammad. The work is structured into six chapters, with shorter introduction and conclusion sections. However, the length of these two sections belies the depth of material contained therein. In the introduction, Ali maps out the scope of her project: a diachronic study of the biographies of Muhammad. She argues for the increasing dialogic between non-Muslim and Muslim views of the Prophet, especially since the nineteenth century. Her statement of what she chose to exclude is greatly appreciated, for it helps point out that there is a great diversity of Muslim thought concerning Muhammad. By making the breadth of the material omitted explicit, she allows the reader to understand in more concrete terms her statement that “[religious] traditions have always been internally heterogeneous” (p. 3). The first chapter focuses on questions of constructing a historical Muhammad. Ali begins with a basic outline of the Muslim narrative version of his life story, but immediately begins to bring up some of the issues, both in terms of the sources and the narrative’s neatness. She explicitly mentions Hagarism and the more recent work of Fred Donner in laying out the historical context of Muhammad. She then deftly works through this scholarship, giving the ...